Surface-Functionalizable Plant-Derived Extracellular Vesicles for Targeted Drug Delivery Carrier Using Grapefruit - Moon, Kyunghwan; Hur, Jihyeon; Kim, Kwang Pyo; Lee, Kangwon; Kang, Ji Yoon (John Wiley and Sons Ltd, 2023)
Recently, membrane-modified mammalian exosomes have been considered strong candidates for targeted drug delivery carriers because of their biocompatibility, biodistribution, and low immune response. However, the widespread utilization of exosomes still requires overcoming several challenging issues, including low stability, high production cost, and low mass productivity. Therefore, artificial extracellular vesicles (EVs) derived from cell membranes or liposomes containing various lipids have been suggested. However, only a few meet the demands of cost-effective mass production and durability of EVs. Therefore, this study investigates the feasibility of replacing mammalian cell exosomes and liposomes with plant-derived extracellular vesicles (pEVs) as targeted drug delivery carriers. They are characterized by nontoxicity, high stability, and high yield. Adding a functionalizable lipid moiety with a maleimide group at the membrane of grapefruit-derived pEVs imparts targeting ability. The targeting function can be easily enhanced by attaching an aptamer using click chemistry. Indeed, treatment of brain cells with pEV-aptamers (hCMEC/D3 and U87MG) confirms that aptamer functionalization of pEV enhanced selective cellular uptake. Functionalization of the pEV membrane using aptamer is expected to be effective in providing low-cost and mass-producible targeted drug delivery carriers with similar efficacy as mammalian exosomes or liposomes.